Liquid metal dealloying of titanium-tantalum (Ti-Ta) alloy to fabricate ultrafine Ta ligament structures: A comparative study in molten copper (Cu) and Cu-based alloys. (June 2020) - Song, T.; Tang, H.P.; Li, Y.; Qian, M.
Highlights: The use of molten eutectic Cu28Ag72 and molten Cu20Ag40Bi40 can profoundly reduce the dealloying temperature vs. in molten Cu. Ultrafine open porous Ta structures with ligament width down to 73 ± 19 nm were fabricated across a 1-mm thick section. The melt temperature dictates the dealloying microstructural length scale in molten Cu but not necessarily in a molten Cu-based alloy. The molten alloy design provides more flexibility to microstructural length scale control by liquid metal dealloying. Abstract: We report dealloying of Ti60Ta40 (wt.%) in molten copper, eutectic Cu28Ag72 alloy and Cu20Ag40Bi40 alloy for the fabrication of ultrafine Ta ligament structures across a 1-mm thick section. When dealloyed in molten Cu and Cu20Ag40Bi40, the melt temperature dictated the length scale of Ta ligaments, which decreased exponentially with decreasing temperature. Conversely, dealloying in molten eutectic Cu28Ag72 alloy led to complex Ta ligament structures due to the enhanced surface diffusivity of Ta by Ag. Ultrafine (<100 nm) Ta ligament structures were produced by dealloying in molten Cu20Ag40Bi40 at 650 °C due to both low melt temperature and low surface diffusivity of Ta.